How Islamic work-life balance mediates work-family conflict and enhances employee performance in religious-based workplaces - Wati, Intan Ratna; Fatimah, Anna; Almadana, Aulia Vidya; Winata, Lanita (University of Islam Malang, 2025)
Work-family conflict often makes employees feel stressed and tired, which can reduce their performance at work. However, there is still a lack of studies on how Islamic work-life balance can help employees handle this problem, especially in hospitals where religious values are very important. In fact, most existing research focuses on general work-life balance, with very few studies exploring it from an Islamic perspective. This study aims to examine whether Islamic work-life balance (IWB) can mediate the negative effect of work-family conflict (WFC) on employee performance (EP). Data were collected from Islamic hospital staff and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that WFC has a strong negative effect on EP, while IWB has a positive effect on EP and can also weaken the negative effect of WFC on EP. This means that when employees have better Islamic work-life balance, they can manage work and family demands more calmly and still perform well. The more employees feel supported by Islamic work-life balance, the more they can focus on their work and achieve higher performance, even when facing strong work-family conflicts. These findings show that IWB is not only important for personal well-being but also helps improve overall organizational outcomes in religious-based workplaces.